Breakthrough applications of porous organic materials for membrane-based CO2 separation: a review - Cao, Yan; Taghvaie Nakhjiri, Ali; Ghadiri, Mahdi (Frontiers in Chemistry, 2024)
Over the last decades, porous organic materials (POMs) have been extensively employed in various industrial approaches including gas separation, catalysis and energy production due to possessing indisputable advantages like great surface area, high permeability, controllable pore size, appropriate functionalization and excellent processability compared to traditional substances like zeolites, Alumina and polymers. This review presents the recent breakthroughs in the multifunctional POMs for potential use in the membrane-based CO2 separation. Some examples of highly-selective membranes using multifunctional POMs are described.Moreover, various classifications of POMs following with their advantages and disadvantages in CO2 separation processes are explained. Apart from reviewing the state-of-the-art POMs in CO2 separation, the challenges/limitations of POMs with tailored structures for reasonable application are discussed.